What changed when Ugandan farmers rated input quality and local vendor services - Van Campenhout, Bjorn; Miehe, Caroline; Spielman, David J.; Sparrow, Robert (The Conversation, 2022)
Each agricultural season, small-scale maize farmers in southeastern Uganda face the same dilemma. Should they shell out a few extra shillings and buy commercial maize seed from the nearby agro-input shop, or should they just plant seed saved from the previous harvest?